PERBANDINGAN PERTUMBUHAN TANAMAN TEBU (Saccharum officinarum L.) DENGAN SISTEM PENANAMAN SINGLE ROW DAN DOUBLE ROW - Mundhir Muktafa; Anna Kusumawati; Dwi Aryani Suryaningrum; Azhari Rizal; Muhammad Mustangin; Ratna Sri Harjanti; Yunaidi Yunaidi (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2023)
Single row and double row are sugarcane planting systems commonly used for cultivating sugarcane. Sugar cane is a tropical plant that is used as raw material for making sugar. Different sugarcane planting systems can cause different growth of sugarcane plants. The aim of this research is to determine the differences in sugarcane plant growth using single row and double row planting systems. This research was carried out using a non-factorial randomized block plan consisting of 2 treatments, namely single row and double row planting systems with 6 blocks in each treatment with a total of 150 plants per treatment. Observational variables included plant height, stem diameter, number of leaves, number of tillers, number of internodes, stem weight per meter and population. The data obtained were analyzed using the t-test using a level of 5%. The results showed that the one-line treatment had a significant effect on the parameters of plant length, number of tillers, stem weight per meter, and population but did not produce significantly different results on the parameters of stem diameter, number of leaves, and number of internodes